Frontline evaluation: Atezolizumab–bevacizumab versus lenvatinib for BCLC stage B hepatocellular carcinoma exceeding the up‐to‐seven criteria - Masamichi Kimura; Koji Nishikawa; Jun Imamura; Kiminori Kimura (Cancer Medicine)
Abstract Introduction This study aimed to evaluate the efficacy and safety of atezolizumab combined with bevacizumab (Atez/Bev) compared to lenvatinib (LEN) as first‐line systemic therapy for patients with Barcelona Clinic Liver Cancer (BCLC) stage B hepatocellular carcinoma (HCC) exceeding the up‐to‐seven criteria threshold, who are typically unsuitable for transarterial chemoembolization (TACE). Methods A retrospective analysis was conducted on 49 consecutive patients with HCC treated at Tokyo Metropolitan Komagome Hospital between May 2018 and October 2023. The patients were divided into two groups: the Atez/Bev group (21 patients) and the LEN group (28 patients). Eligibility criteria included Child‐Pugh A classification, no prior systemic therapy, and ineligibility for resection, ablation, or transplantation. Treatment outcomes were assessed through periodic imaging and laboratory tests, evaluating OS, PFS, ORR, and disease control rate (DCR). Results Both groups demonstrated comparable baseline characteristics, with a median follow‐up of 15.4 months. No significant difference was observed in OS between the Atez/Bev and LEN groups (median OS: 19.80 vs. 22.20 months, p = 0.763). The median PFS was 10.23 months for Atez/Bev and 7.20 months for LEN (p = 0.343). There were no statistically significant differences in ORR or DCR between the two groups. Common adverse events included elevated AST and ALT levels, with no significant difference in the overall rate of adverse events between the groups. Conclusions Atez/Bev and LEN demonstrated comparable efficacy and safety as first‐line systemic treatments for patients with BCLC stage B HCC exceeding the up‐to‐seven criteria. Both therapeutic options are viable for this population, though further large‐scale prospective studies are required to confirm these findings.